Respostas
respondido por:
4
primeiro vamos achar a razão:
q = a2/a1
q = 3/1
q = 3
Logo:
a1 = 1
q = 3
n = 7
an = a1 . q^(n-1)
an = 1 . 3^(7-1) como 1 vezes qualquer número é ele mesmo:
an = 3^6
an = 729
Logo o sétimo termo é 729.
Bons estudos
q = a2/a1
q = 3/1
q = 3
Logo:
a1 = 1
q = 3
n = 7
an = a1 . q^(n-1)
an = 1 . 3^(7-1) como 1 vezes qualquer número é ele mesmo:
an = 3^6
an = 729
Logo o sétimo termo é 729.
Bons estudos
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás